I DON’T KNOW THE WORDS: TEACHER NARRATIVES ON STUDENT CHALLENGES IN CREATIVE WRITING (EVIDENCE FROM BONE, SOUTH SULAWESI) - Febriana, Mia; Yusuf, Munawir; Subagya (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
This study aimed to explore the challenges faced by students in creative writing. A qualitative narrative approach was employed, gathering data through open-ended questionnaires and transcription. The narratives in this study were collected from seven English teachers from seven different schools in Bone Regency, South Sulawesi Province. The data was analyzed using the constant comparative method. The primary difficulties encountered by students include a limited vocabulary, student motivation, and a lack of ideas for writing. Teachers provided solutions such as supplying related vocabulary pertinent to the theme, giving students a foundation to build upon. Additionally, assigning writing themes related to the student’s immediate environment was found to stimulate their exploration and creativity. The study reveals that students’ challenges in creative writing are predominantly rooted in linguistic limitations, motivation, and a lack of ideas. The implications suggest a need for integrating targeted vocabulary development and contextually relevant themes in creative writing curricula, emphasizing the importance of aligning teaching strategies with students’ linguistic abilities and environmental experiences.Keywords: creative writing, student challenges, teacher narratives